Caracterización del business capital de las cooperativas de crédito a través del análisis Delphi - Seguí-Mas, Elies; Ricardo J. , Server Izquierdo (REVESCO. Revista de Estudios Cooperativos, 2010)
Business Capital has constantly been used to explain the beneficial impact that some banking companies have on the economic development. Credit cooperatives, which are singular in our financial system, posses certain assets with their own features. Thus, corporate reputation, social relationships and interaction with public administration and media shape credit unions in such a way that it is worth to be studied. By means of Delphi analysis this work identifies the singularities of business capital in credit cooperatives. Among these specialties are remarkable the proximity and members’ participation (strength) and their reputation (weakness). Intangible business assets stand for a high value in credit cooperatives, especially with regard to the proximity. In order to foster business capital in credit cooperatives it is key to enhance their financial services and alliance policy.